Pengaruh Job Demands dan Job Resources terhadap Work Engagement pada Tenaga Kependidikan Universitas Wijaya Kusuma Surabaya - Anisa Aprilianingsih; Agus Frianto (Jurnal Ilmu Manajemen, 2022)
The study aims to determine the effect of job demands and job resources on work engagement in educational institutions. This study sample used 51 employees. Data collection is obtained through a survey. The data analysis used in this study is a validity test, reliability test, classical assumption test, and multiple linear regression using SPSS version 26. The results showed that job demands, and job resources simultaneously significantly affected work engagement. Partially, job demands have a negative and significant effect on work engagement. Job resources have a positive and significant impact on work engagement. Companies should consider providing mentoring when there is additional work, job changes or job rotation for employees to reduce workload due to lack of understanding of the job. Superiors or colleagues can do mentoring by the field of work. Work can be more efficient, and job resources can also be maintained and improved. When employees have achieved high work involvement, it will positively impact work and the organization in improving performance to achieve organizational goals.